Effect of citric acid in low nutrient diet on growth and bone mineral metabolism of broiler (Bangladesh Journal of Animal Science, 2021)
The study was conducted to observe the performance of broiler in low level of dietary nutrients but using citric acid (CA) as feed additive. A total of 240 day old straight run broiler chicks (COBB 500) were randomly distributed into eight groups, with three replicate cages having 10 birds in each. Control diet (Group 1) was formulated with corn-soybean based ingredients contained 22.7% CP and 3213 kcal ME/kg. Other dietary Groups 2, 3, 4, 5, 6, 7 and 8 were control+0.5% CA, control+4% low protein and energy, control+4% low protein and energy with 0.5% CA, control+8% low protein and energy, control+8% low protein and energy with 0.5% CA, control+12% low protein and energy and 12% low protein and energy with 0.5% CA, respectively. At the age of 31 days 8% lowering the protein and energy could compensate by the addition of citric acid (group 6). There was no significant difference of total feed intake among the groups. As live weight 8% lowering the protein and energy could compensate the feed efficiency when addition of CA. Tibia ash was determined in first four groups that were 44.2, 49.5, 46.8 and 47.1% in group 1, 2, 3, and 4, respectively. The mortality was 0.0% during the whole experimental period. The cost of production (BDT/kg broiler) was lowest in group 8, that means lowering protein and energy reduces feed cost. It may be concluded that diets containing low protein and energy up to 8% but addition of 0.5% citric acid would compensate the performance of broiler, but 12% reduction of energy and nutrients is cost effective.Bang. J. Anim. Sci. 2021. 50 (1):36-42